Clinical pathways for inborn errors of metabolism: warranted and feasible - Demirdas, Serwet (BioMed Central, 2013)
Inborn errors of metabolism (IEMs) are known for their low prevalence and multidisciplinary care mostly founded on expert opinion. Clinical pathways are multidisciplinary tools to organise care which provide a clear route to the best care and improve communication. In 2010 the Dutch Society for Children and Adults with an Inborn Error of Metabolism (VKS) initiated development of clinical pathways for inborn errors of metabolism. In this letter to the editor we describe why it is warranted to develop clinical pathways for IEMs and shortly discuss the process of development for these pathways in the Netherlands.